2013
DOI: 10.12799/jkachn.2013.24.1.87
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Marriage Migrant Women's Korean Language Ability, Self-esteem, and Acculturative Stress on Their Family Health: Focused on Mediating Effects of Marital Adjustment

Abstract: Purpose: This study was conducted for the purpose of a structural model analysis of family health of women who came to Korea for being married to Korean men. Methods: The data were collected from 260 immigrant women at multicultural centers located in C and B cities from May 10th to 30th, 2012. The variance analysis on the samples was conducted by using the maximum likelihood minimization function with AMOS 7.0. The fitness was evaluated by means of the SRMR, RMSEA, CFI, and TLI with a 90% confidence interval.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Thao (2016a) examined the level of acculturative stress and depression among immigrant Vietnamese wives in South Korea and revealed that acculturative stress was a strong predictor of depression. This finding is consistent with other studies that have assessed the same issue (Castro & Murray, 2010;Lee et al, 2013;Lin & Hung, 2007).…”
Section: Acculturative Stress and Life Satisfaction Of Immigrant Viet...supporting
confidence: 93%
“…Thao (2016a) examined the level of acculturative stress and depression among immigrant Vietnamese wives in South Korea and revealed that acculturative stress was a strong predictor of depression. This finding is consistent with other studies that have assessed the same issue (Castro & Murray, 2010;Lee et al, 2013;Lin & Hung, 2007).…”
Section: Acculturative Stress and Life Satisfaction Of Immigrant Viet...supporting
confidence: 93%
“…And social support was increased by 3.56 points after performing from 3.25 points before the program is running, and after the 4 week of the program it was continuously increased up to 3.78 points. In this study, a mentor in a mentoring program with the same nationality as the person first immigrants who have experienced other cultures and learn through training and culturally appropriate skills and behaviors [25]. Korea Culture and parenting has got a wide range of information, including a lack of knowledge and information associated with the mother, linking the community, counseling believed such a case the result is shown to be a collaborative effort with each other.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution took place when the scores in all areas reached or exceeded the “average” level of three points. The participants’ level of Korean communication ability ( Lee et al, 2013 ) was evaluated using a 5-point scale (1 = “not at all” to 4 = “very good”), encompassing four items related to speaking, listening, reading, and writing. The completion time for the questionnaire was approximately 15 to 25 min.…”
Section: Methodsmentioning
confidence: 99%